Uso de substâncias psicoativas, transtornos mentais comuns e ideação suicida em estudantes de psicologia - Vasconcelos, Maria Clara Prado (2023)
The number of young adult enrollments in higher education has grown exponentially. The new reality of academic life imposes many challenges and changes related to the routine, responsibilities and social demands of this context can generate intense emotional overload in young people, which, with the reality of the university environment, if not cared for with the necessary support and attention, leads to psychological suffering, generating symptoms such as stress, anguish, changes in the sleep-wake cycle, ideation and risk of suicide, among others. Undergraduate courses that involve contact with other people's psychological suffering or that study human subjectivity correlate with a certain vulnerability and can increase the chances of developing a mental disorder. The present study aimed to verify the relationship between suicidal ideation, common mental disorders, use of psychoactive substances and social, demographic and economic variables in psychology students at a Federal University in the interior of Ceará. This research consisted of a quantitative, cross-sectional and exploratory study. 121 students participated in the study. A demographic and socioeconomic questionnaire was applied, the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), which aims to assess the use of psychoactive substances, the Self-Reporting Questionnaire (SQR-20), which aims to investigate the presence of common mental disorder and the Beck Suicidal Ideation Scale (BSI), to assess suicidal ideation among participants. As a result, it was observed that 39.7% of the students participating in the research showed signs of Common Mental Disorders. The consumption of alcohol, marijuana and tobacco had the highest means and standard deviation among the substances investigated. These average and dispersion values indicate low risk to moderate risk for these substances. The average suicidal ideation score was 3 points (SD: 5.62), ranging from 0 (minimum value) to 32 (maximum value). Students with higher scores in CMDs and in relation to marijuana use had higher scores in suicidal ideation. Furthermore, students with non-heteronormative sexual orientations had higher averages in relation to suicidal ideation. From what was exposed in this work, it was possible to identify that psychology students have a high rate of psychological distress, which is expressed in high values of Common Mental Disorders among these young people. In addition, considerable consumption of alcohol, tobacco and marijuana was observed.